Decision Support System for Service Development Priority Selection at Pitcar Service Using the ELECTRE Method - Nur Aela Dewi; Khairun Nisa Meiah Ngafidin (Edu Komputika Journal, 2024)
The increasing competition in the automotive industry is pushing companies like Pitcar Service, a car workshop in South Purwokerto, to develop efficient and quality services. However, this workshop faces limitations in assets, materials, and capabilities. Therefore, Pitcar Service requires a Decision Support System (DSS) to assist in determining the priority for service development. The DSS helps identify and prioritize the most important services or those that have the greatest impact on business growth. By focusing on strategic development that provides significant added value, the company can achieve its strategic goals in line with the company's vision. The method used in this study is ELECTRE (Elimination and Choice Translation Reality), a suitable algorithm for designing a decision support system. This method allows pairwise comparisons between alternatives based on relevant criteria. The assessment is done by comparing each criterion individually to determine whether an alternative dominates other alternatives. With this method, the assessment of workshop services can be done objectively. The service alternatives considered include Workshop Service, Pick Up Service, Emergency Service, Home Service, Variations, and B2B Services. Meanwhile, the criteria used for the assessment include the number of requests, average income per job, tool usage, the number of mechanics, and processing time. The calculation results show that B2B Service is the main priority for service development with a dominant aggregation matrix result is 2.